Adherence Clubs to Improve Hypertension Management in Nigeria: Clubmeds, a Feasibility Study. Issue 1 (16th March 2022) - Isiguzo, Godsent C.; Santo, Karla; Panda, Rajmohan; Mbau, Lilian; Mishra, Shiva R.; Ugwu, Collins N.; Virani, Salim S.; Odili, Augustine N.; Atkins, Emily R.
Background: Hypertension control remains a significant challenge in reducing the cardiovascular disease burden worldwide. Community peer-support groups have been identified as a promising strategy to improve medication adherence and blood pressure (BP) control. Objectives: The study aimed to evaluate the feasibility and impact of adherence clubs to improve BP control in Southeast Nigeria. Methods: This was a mixed-methods research involving a formative (pre-implementation) research, pilot study and process evaluation. Hypertensive patients in two communities were recruited into peer-support adherence clubs under the leadership of role-model patients to motivate and facilitate medication adherence, BP monitoring, and monthly medication delivery for six months. The primary outcome was medication adherence measured using visual analogue scale (VAS), with BP level at six months as a key secondary outcome. Results: We recruited a total of 104 participants. The mean age was 56.8 (SD–10.7) years, 72 (69.2%) were women, mean BP was 146.7 (SD–20.1)/86.9 (SD–11.2) mmHg, and the mean percentage of medication adherence on the VAS was 41.4% (SD–11.9%). At six months, 67 patients were assessed; self-reported adherence on the VAS increased to 57.3% (SD–25.3%) (mean difference between baseline and follow-up of 15.5%, p < 0.0001), while the mean BP decreased to 132.3 (SD–22.0)/82.9 (SD–12.2) mmHg (mean difference of 13.0 mmHg in systolic BP, p < 0.0001 and of 3.6 mmHg in diastolic BP, p = 0.02). Five in-depth interviews and four focus groups discussions were conducted as part of the qualitative analyses of the study. The participants saw hypertension as a big issue, with many unaware of the diagnosis, and they accepted the CLUBMEDS differential service delivery (DSD) model concept in hypertension. Conclusions: The study demonstrates that the implementation of adherence clubs for hypertension control is feasible and led to a statistically significant and clinically meaningful improvement in self-reported medication adherence, resulting in BP reduction. Upscaling the intervention may be needed to confirm these findings.